Feed Type and Level of Viterna on Body Weight, Percentage of Carcass, Non-Carcass and Abdominal Fat of Broiler Chickens - Dappa, Enjelina; Mulyantini, N. G. A; Theedens, Jonas F; Telupere, Frangky M. S (JURNAL ILMIAH PETERNAKAN TERPADU, 2024)
This study aims to examine the effects of different types of feed and level of viterna on the final body weight, carcass percentage, non-carcass, and abdominal fat of broiler chickens. The method used was a 2x4 factorial Completely Randomized Design. The first factor was 2 types of commercial feeds (J1=A and J2=B). The second factor was 4 levels viterna (P0=0cc; P1=1.5cc; P2=3cc; P3=4.5cc/l drinking water). There were 8 treatment combinations with 4 replications, and each replicate consist of 4 chickens, a total of 128 broilers was used. The treatment combinations were as follows: J1P0=feed A without viterna in drinking water, J1P1= feed A+1.5cc viterna/l water, J1P2 = feed A+ 3cc viterna/l water, J1P3= feed A + 4.5cc viterna/l water, J2P0 = feed B without viterna in drinking water, J2P1= feed B + 1.5cc viterna/l water, J2P2=feed B + 3cc viterna/l water, J2P3= feed B + 4.5cc viterna/l water. The measured variables were final body weight, carcass percentage, non-carcass, and abdominal fat. Data were analyzed using a variance test at a significance level of 5%, treatments that were significant (P≤0.05) followed by the Duncan Multiple Range Test.  The results showed that there was no interaction (P>0.05) between feed type and viterna level on all parameters. In conclusion, differences in the type of feed, and viterna level, also interaction between the two factors did not make a difference to the final weight, percentage of carcass, non-carcass, and abdominal fat of broiler chickens.